Design and synthesis of magnetically separable CuFe2O4/MoS2 p-n heterojunction for photocatalytic efficiency of Rhodamine B degradation - Atacan, Keziban; Güy, Nuray; Özacar, Mahmut (Colloid and interface science communications, 2021)
A visible active CuFe2O4/MoS2 magnetic nanocomposite was successfully synthesized via hydrothermal technique. The synthesized photocatalysts were perused by X-ray diffraction, Fourier transform infrared spectroscopy, Scanning electron microscopy, Transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), UV–vis diffuse reflectance/absorbance spectroscopy and Vibrational sample magnetometer measurements. Also, the photocatalytic efficiency was investigated by photocatalytic degradation of Rhodamine B under visible light illumination. As a result, CuFe2O4/MoS2 was showed excellent reusability through magnetic separation and its degradation rate of Rhodamine B as high as 98.5%. In addition, the mechanism of the Rhodamine B degradation elucidated that•O2− radicals had the most significant role in the photocatalytic proceses for CuFe2O4/MoS2 composite. The proposed mechanism for photocatalytic activity over the CuFe2O4/MoS2 composite under the visible light irradiation. [Display omitted] •CuFe2O4/MoS2 p-n heterojunction was prepared via hydrothermal method and characterized.•The CuFe2O4/MoS2 p-n heterojunction was used for photocatalytic efficiency of Rhodamine B degradation.•The degradation yield of Rh B was about 99% after 60 min under visible light.•CuFe2O4/MoS2 was showed excellent reusability through magnetic separation.